PENERAPAN PERATURAN BUPATI JOMBANG NOMOR 41 TAHUN 2019 PADA PROGRAM MUATAN LOKAL KEAGAMAAN: Studi Kasus di SDN Tugu Kepatihan 2 Jombang - Rozaqi, Muhammad Lutfi; Umam , Khoirul; Arini, Aida (EL-Islam, 2022)
Abstract: This article examines the application of Jombang district head regulation number 41 of 2019 to the local religious content program. Religious local content is a compulsory charge subject at the elementary and junior high school level, which was promulgated in Jombang district regulation number 09 in 2016 with the hope of the realization of "religious Jombang". This study discusses the extent to which the Jombang buapati regulation number 41 of 2019 is applied to the local religious content program as well as the factors that influence the application of Jombang regent regulation number 41 in 2019 . This article uses a qualitative field research approach based on observation, interviews, and documentation with qualitative descriptive analysis and checking the validity of data and triangulation .The results of this study are in the form of technical aspects and mechanisms which include the understanding, purpose and objectives of local religious content, competency standards of educators and student competency standards that must be achieved, process and assessment standards, number of teaching hours and honoariums . Local content in Jombang does not only refer to Islam, but other religions such as the Christian religion are also the same. Factors influencing the adoption of the regent's regulations are resources, trends, bureaucracy and communication.